Wacana Berita Bertajuk Korupsi dalam Situs Indonesiana dan Implikasi Pembelajaran Analisis Wacana - Rahmat Prayogi (Universitas Muhammadiyah Kotabumi, 2017)
The research discussed about text, discourse practice, and sociocultural practie of coruption discourse in Indonesiana site, and its implication to discourse analysis learning in University. The method used in this research was qualitative method with critical discourse analysis by Norman Fairclough. Based on the result of the research and discussion, text components in every discourse reveals the critical facts in society. Meanwhile, discourse practice denotes external component which affect text production process so the discourse become more comprehensive. Then, sociocultural practice or social knowledge which becomes the framework of writer could emphasize the discourse result. The result of the research could be used as an example step to discourse analysis by Norman Fairclough.